Magical and religious representations in the confessional field of modern Belarusian society - Shkurova, Alena V.; Reut, Elizaveta V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article is devoted to analysing the peculiarities of religious beliefs in Belarus. A brief overview of the adherence of confessions’ representatives to religious ideas is given. The specificity of the perception of the confessional truths by various categories of the religious population is analysed. In the process of analysis, the ratio of magic and mysticism in the context of the religious system is touched upon. А hypothesis that confessional affiliation does not exclude a tendency to magical ideas is built within the framework of the article, and a conclusion about the features of the construction and reproduction of magical and religious thinking is made.
Keywords: religious representations; magical thinking; mystic; religious systems; mystical experience; religious ideas; traditional denominations